On the Majalengka Sundanese: Lexical Variations and Morphology - Purwitasari, Ana (Fakultas Bahasa Seni dan Budaya, 2024)
Majalengka Sundanese has been heavily influenced by Indonesian and Javanese for having a Javanese enclave. On the contrary, Indonesian influences vocabulary spoken mainly in Majalengka, Sukahaji, Panyingkiran, Cigasong and Kadipaten sub-districts as those regions are located near from the city centre of Majalengka Regency. Majalengka Sundanese words got shaped by Javanese are natively uttered in the Javanese enclave, referring to Patuanan rural village in Leuwimunding sub-district. Those are also uttered in Jatitujuh rural village in Kertajati sub-district and Parapatan rural village in Sumberjaya sub-district for sharing border with Indramayu and Cirebon regencies as home of Javanese speakers. The data were gathered by interviewing natives. Those words altered by Javanese include (1) pertelon